Moringa Leaves: A sustainable Food and healthresource - Sutrisno Adi Prayitno (Academic Letters, 2025)
Moringa oleifera, commonly referred to as the "miracle tree," is a plant with a variety of benefits, including its potential as a source of food and a means to enhance human health. Its use in traditional medicine extends back millennia, and in recent years, it has gained significant attention in research communities. The plant has yielded a wealth of data suggesting that it can address critical global challenges related to food and health sustainability. The exploration of Moringa for the benefit of the food industry is primarily driven by the presence of numerous bioactive compounds that offer global benefits, particularly in supporting sustainable food security. Moringa possesses considerable potential for advancement within the food industry, serving not only as a primary raw material but also as an ancillary ingredient, thereby enhancing the nutritional value and health benefits of products.